International Organization Logos: A Semiotic Prespective - Setiadi, Fajar; Dr. Maryadi, Dr. Maryadi.MA (2016)
ABSTRACT Organizations under United Nation has its own logo as their identity. The objectives of this research are to describe the events and to find the meanings presented by the International Organization Logos. The data is the International Organization Logos which are collected from International Organization Logos under United Nation official website as many as 16 pictures. In collecting the data, the researcher ccollects the International Organization Logos from the United Nation Organization website and classify the logo based on its containing of world events issues. The theories used are the Pierce theory and Saussure theory. Pierce emphasized his theory on the representamen, interpretant and object. Then, Saussure emphasized his theory in analyzing sign using the signifier and signified criteria. The type of the research is qualitative interpretative. In analyzing the data there are aanalyzing the meaning of the index used to represent the logos by using Peirce's theory then define the relation between the events and the index used on the logos by aapplying the Saussure's theory by using signifier and signified to identify the meaning of the index. This research shows that (1) The signifier is the visual shape of the logo and signified is the symbol of the picture as the representation of its event. The event of its agency usually pictured with the picture who stand in the midlle or it cleared with the bold and capital acronyim of the agency's name. (2) the meaning of International Organization Logos showed with the representment as the visual shape also, interpretant the interpretation of each picture within the logo and object is the purpose or the field of the organization. Keywords: Semiotics, International Organization Logos, Pierce and Saussure theory